(untitled) (Altre Modernità, 2012)
This article discusses and exemplifies the ways in which Italian as a product of translation differs from spontaneous Italian. In particular, the translated language would seem to be characterised by more options than native Italian, due to free variation with the options influenced by the language of the original text. Though somehow a physiological byproduct of the translation activity, interference should be monitored, as it may give rise to different interpretations from those of the original text and/or to stylistic choices not appropriate to the context.